Hyperparathyroidism and increased fractional excretion of phosphate predict allograft loss in long-term kidney transplant recipients - Sumanee Prakobsuk (2018)
© 2016, Japanese Society of Nephrology. Background: After kidney transplantation, fibroblast growth factor-23 (FGF-23) normally returns to baseline within 1 year whereas hyperparathyroidism persists in most kidney transplant (KT) recipients. As a result, serum phosphate remains relatively low in association with increased serum calcium and urinary phosphate excretion when compared to chronic kidney disease patients. The relationship between mineral metabolism and outcomes in long-term KT recipients has not been extensively studied. This study investigated whether the alteration in mineral metabolism influenced graft survival in long-term KT recipients. Methods: This study included 273 KT recipients after 1 year of transplantation. Mineral parameters were obtained at the time of enrolment and patients were followed prospectively for an average of 71 months. Results: Graft loss (death-censored) occurred in 41 (15%) patients. In univariate analysis, deceased donor transplantation, decreased serum albumin and estimated glomerular filtration rate, increased serum phosphate, parathyroid hormone (PTH), FGF-23 and fractional excretion of phosphate (FePi) predicted future allograft loss. After adjustments for cardiovascular disease risk factors, donor type, dialysis vintage, serum albumin and allograft function, only increased PTH and FePi remained associated with the outcome. Relationships between increased serum phosphate and FGF-23 with graft survival were lost after adjustments. Adjusted survival curves revealed the association between PTH > 90 pg/mL and FePi > 20% with worse graft survival. Conclusions: Hyperparathyroidism and increased FePi predicted allograft loss in long-term KT recipients.